Xeroderma Pigmentosum: Clinical and Genetic Features and Therapeutic Approaches - Tatyana S. Belysheva; Tatyana V. Nasedkina; Iryna S. Kletskaya; Anastasiya S. Volkova; Vera V. Semenova; Timur T. Valiev (Вопросы современной педиатрии)
Xeroderma pigmentosum is rare genetic disorder characterized by increased skin sensitivity to damaging ultraviolet (UV) light. First symptoms manifest at early age in most cases (up to 75%). Chronic damage due to sun exposure is common, it has different stages of changes and risk of further development of malignant tumors that depends on the gene involved. Additionally to skin manifestations there are various neurological disorders such as progressive cognitive dysfunctions, sensorineural hearing loss, ataxia, pyramid and extrapyramidal disorders, areflexia. Treatment of patients with xeroderma pigmentosum is mostly symptomatic and preventive (protection against UV). Nowadays targeted medications for DNA repair and increasing cells resistance to UV light, thus preventing the oncological diseases, are under development.